Application of the Tilawati Method on Speed ​​of Reading Al - Qur'an at the Al - Qur'an Education Park (TPQ) Sidoarjo Regency: Penerapan Metode Tilawati pada Kecepatan Membaca Al – Qur’an di Taman Pendidikan Al – Qur’an (TPQ) Kabupaten Sidoarjo - Purnamasari, Risda Nur; Nadlif, Ainun (Indonesian Journal of Education Methods Development, 2022)
This study aims to determine the application of the tilawati method in learning to read the Qur'an at TPQ Nurul Huda and explain the steps for applying learning to read the Qur'an at TPQ Nurul Huda using the tilawati method. In this case, the research subjects are the head of TPQ, TPQ teachers and students at TPQ Nurul Huda Sidoarjo. Data collection techniques are interviews, observation and documentation. The data sources are primary and secondary data. The results of this study are the method in this learning is carried out through 3 stages, namely initial activities, core activities and closing activities. The three activities that have been carried out in a learning using the tilawati method are in accordance with the steps of a learning that are in the tilawati method of learning Al-Qur'an strategy books. And the methods that have been implemented by these clerics are in accordance with the tilawati method manual, which is a learning carried out using classical and individual methods. By using the tilawati method at TPQ, Nurul Huda Sidoarjo has its own target in learning tilawati to make students fast in reading the Qur'an. The fast learning target that will be taken is 1 year 2 months to complete all tilawati volumes starting from volume 1 to volume 6. So each volume is taken within 2 months to complete.